2000
DOI: 10.2169/internalmedicine.39.188
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus Isolated from Blood Samples of a Patient with Pulmonary Aspergilloma after Embolization.

Abstract: Aspergillus DNAwas detected by PCR in the serum sample of a 78-year-old man and galactomannan antigen ofAspergillus by sandwich ELISA was found. However, the infiltrative hyphae were not detected by the histopathologic examination of the lung. He developed hemoptysis, which required embolization of bronchial arteries. Aspergillus fumigatus was isolated from blood samples after embolization by the lysis centrifugation method. To our knowledge, this is probably the first case in which Aspergillus spp. has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…from blood is usually related to a central venous catheter infection, to cardiac surgery, or, for neutropenic patients, to pulmonary infection. Positive blood cultures have been reported for one case of pulmonary aspergilloma (10). The rarity of the isolation of Aspergillus spp.…”
Section: Species Of the Genusmentioning
confidence: 99%
“…from blood is usually related to a central venous catheter infection, to cardiac surgery, or, for neutropenic patients, to pulmonary infection. Positive blood cultures have been reported for one case of pulmonary aspergilloma (10). The rarity of the isolation of Aspergillus spp.…”
Section: Species Of the Genusmentioning
confidence: 99%
“…Fungemia caused by Aspergillus species is worth of publication because there are limited data in the literature. 5,[8][9][10][11][12][13] Blood cultures are rarely positive in disseminated aspergillosis. 8,14 PCR assay is more sensitive for the detection of Aspergillus in blood when compared with culture.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Although the PCR assay has lots of superiority to the other methods, increased sensitivity may cause some limitations. Seki et al 5 suggested that extracting of Aspergillus DNA from blood may be the result of the circulation of fungal cell or DNA particles in blood rather than fungemia. Because of this limitation, DNAemia cannot be ruled out in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemoptysis is the major life-threatening acute clinical condition caused by PA. There is also some risk of developing invasive aspergillosis or fungal septicemia, which have even higher morbidity and mortality (5,6). Treatment and follow-up of patients with PA still lack a well-defined evidence-based algorithm.…”
Section: Introductionmentioning
confidence: 99%